Phytofluene from Physalis peruviana as promising anti-TB via InhA of Mycobacterium tuberculosis target: an in silico research - Prastiyanto, Muhammad Evy; Aini, Nur Sofiatul; Yuanita Rachmawati (Genbinesia Journal of Biology, 2022)
Tuberculosis (TB) is an infectious disease after severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) in developed countries including Indonesia. Drug resistance becomes major issue worldwide and needs prospective therapeutics development. Plant with medicinal properties including Physalis peruviana is one the promising object to be new anti-TB drug candidate. This study aimed to analyze the inhibitory activity of anti-TB agents from aerial parts of P. peruviana. Ligand and protein samples were obtained from PubChem and RCSB PDB, respectively. The bioactive compounds were evaluated their antibacterial prediction and drug-likeness properties throughout PASS Online and SwissADME webservers. Selected ligands then docked via PyRX and measured the output by binding affinity. Visualization of the best outputs was carried out using BIOVIA Discovery Studio. The result showed that phytofluene had the lowest binding affinity topping the isoniazid as control with -7.2 and -5.1 kcal/mol after targeting enoyl-[acyl-carrier-protein] reductase (InhA) protein of Mycobacterium tuberculosis. This concluded that phytofluene functioned as predictive anti-TB therapeutic candidate. Further in vitro and in vivo studies are needed to validate this outcome.